2022
DOI: 10.1039/d2nj01980a
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, anticancer activity and molecular docking studies of new benzimidazole derivatives bearing 1,3,4-oxadiazole moieties as potential thymidylate synthase inhibitors

Abstract: The present work describes the synthesis and anticancer activity of new benzimidazole derivatives bearing 1,3,4-oxadiazoles as thymidylate synthase inhibitors. The newly synthesized molecules were confirmed by NMR, mass, FT-IR and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…The reactive intermediates 2–5 were synthesized using our previously reported methods with minor modifications. 32 Eugenol ( 1 ), on reaction with ethyl bromoacetate using potassium carbonate in dry acetone, yielded compound 2 (90%), which after reaction with hydrazine hydrate afforded compound 3 (88%). An alcoholic solution of compound 3 in KOH was treated with carbon disulfide at 0–30 °C and then refluxed, followed by acidification using concentrated hydrochloric acid, to yield the key intermediate 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactive intermediates 2–5 were synthesized using our previously reported methods with minor modifications. 32 Eugenol ( 1 ), on reaction with ethyl bromoacetate using potassium carbonate in dry acetone, yielded compound 2 (90%), which after reaction with hydrazine hydrate afforded compound 3 (88%). An alcoholic solution of compound 3 in KOH was treated with carbon disulfide at 0–30 °C and then refluxed, followed by acidification using concentrated hydrochloric acid, to yield the key intermediate 4 .…”
Section: Resultsmentioning
confidence: 99%
“…The reported TS inhibitor 5-fluorouracil (5-FU) was stabilized at the active site through various amino acid residues (SER216, ASN226, ARG50, ARG215, GLY217, CYS195, GLY222, HIS256, ARG175, ASP218, and ARG176). 32 The self-docking was used as a prior docking calculation to generate the docked pose. Then, the induced-fit-docking was applied to generate the final pose which was minimized using the OPLS force field.…”
Section: Resultsmentioning
confidence: 99%
“…The in silico toxicity prediction of compounds 10 and 13 were carried out by pkCSM software [ 42 ], and the results are shown in Table S1 . It was observed that compounds 10 and 13 were less toxic compared to the standard drug erlotinib; the maximum tolerated dose for humans for compounds 10 and 13 was 0.3 and 0.125 mg/kg/day, respectively, which are much higher than the maximum dose for erlotinib (0.002 mg/kg/day).…”
Section: Resultsmentioning
confidence: 99%
“…The anticancer activity was evaluated on two mammalian cell lines, Huh-7 cells (Hepatocellular) and HeLa (Cervical) which were obtained from the American Type Culture Collection (ATCC, Rockville, MD) whereas MRC-5 (Normal human Lung fibroblast cells), were obtained from VACSERA Tissue Culture Unit, Egypt. It was performed according to previously published work [28] using doxorubicin as a positive reference drug.…”
Section: Anticancer Activitymentioning
confidence: 99%